Use of different methods for the evaluation of teat disinfectant products. Issue 1 (31st December 2022) - Fitzpatrick, Sarah Rose; Garvey, Mary; Flynn, Jim; O' Brien, Bernadette; Gleeson, David
ABSTRACT: There are many test methods used to determine the effectiveness of teat disinfectants. The objective of this study was to determine the outcome from the use of three different test methods (BS EN 1656 [laboratory], disc diffusion [laboratory] and an experimental challenge teat swabbing method [in-field]) when evaluating the effectiveness of ten teat disinfectant products. Products were tested against three bacterial strains ( Escherichia [E.] coli [ATCC ® 10536™], Staphylococcus [Staph.] aureus [ATCC ® 6538™] and Streptococcus [Str.] uberis [ATCC ® 19436™]). All products satisfied the requirements of the BS EN 1656 method achieving >10 5 log reductions. Two laboratory methods were consistent in identifying effective products against Staph . aureus and E . coli, whereas, all three methods were consistent in identifying effective products against Str . uberis . Within the two laboratory methods, products containing 2% lactic acid combined with 0.3% chlorhexidine gluconate and 5% lactic acid combined with 0.3% chlorhexidine were within the top four most effective products against Staph . aureus . For Str . uberis, products containing 2.4% lactic acid, 0.29% iodine combined with 0.8% lactic acid and 0.5% iodine (control) were within the top four most effective products. This study has established that effectiveness of teat disinfectant products can be determined by different test methods.